PP.06.04: BIOMECHANICAL MODELING OF ABDOMINAL AORTIC ANEURYSMS BEHAVIOUR AND THE THROMBUS EFFECT ON THR RUPTURE RISK IN XÉNOGRAFT RAT MODEL. (June 2015) - Bouaricha, A.; Djellouli, D.; Baranji, M.; Benhassine, N.; Allaire, E.; Zidi, M.
Abstract : Objective: Current treatments of abdominal aortic aneurysm (AAA) can be achieved either by aortic replacement during surgery or by deploying endovascular prosthesis. Regenerative medicine to substitute these conventional surgery or an endovascular stent constitutes currently a challenge to treat abdominal aneurysm artery (AAA) It is worth reminding that in the case of xénograft in rat, it was shown that cellular therapies with mesenchymal stem cells (MSCs) stabilize the diameter of AAA. At this stage, the study of the mechanical behavior of artery appears necessary to investigate the impact of MSCs therapy on the rupture risk of the arterial wall after treated AAA diameter stabilization. Therefore, each groups of samples (healty, untreated and treated) should be investigated. So, the aim of this paper is to determine the mechanical behavior of already formed healty, untreated and treated abdominal aortic aneurysms and study the effect of the thrombus on arterial wall stiffness and strength in the Xenograft rat model AAA. Design and method: For that, the xenograft rat model that mimics arterial dilatation due to aneurysmal disease is used to study the effects of the proposed cellular therapy. To investigate the changes in the mechanical behavior of the arterial wall, the artery is assumed to be made of a hyperelastic and incompressible material characterized by a strain energy function fitted to the average data set of uniaxial tests of AAA tissue samples. In order to compute the stresses in the artery by using an analytical approach, the 3D aneurysm geometric is obtained based on "parabolic-exponential"profil. Results: When compared to healthy, untreated and treated arteries, the obtained results demonstrate that the cellular therapy stabilizes the geometry of AAAs, improves the stiffness of the tissue and decreases stress variations in the arterial wall. Conclusions: * Based on both in vivo and in vitro data, the study helped to evaluate the ability of MSCs to repair AAA and the Intraluminal thrombus can effectively reduce wall stress in abdominal aortic aneurysms.